FTIR-DRIFTS-based prediction of β-carotene, α-tocopherol and L-ascorbic acid in mango (Mangifera indica L.) fruit pulp - Olale, Kennedy O.; Walyambillah, Waudo; Mohammed, Salim Ali; Sila, Andrew M.; Shepherd, Keith D. (Springer, 2019)
Mango fruits contain substantial vitamins and dietary fibre. Vitamins vary among and within fruits depending on cultivar type and ripening stage. Conventional techniques of vitamins analysis are based on High Pressure Liquid Chromatography, which are costly and laborious. This study evaluated the potential of Fourier transform infrared-diffuse reflectance spectroscopy (FTIR-DRIFTS) technique in predicting β-carotene, α-tocopherol and L-ascorbic acid in pulps of four mango cultivar types (‘Apple’, ‘Kent’, ‘Ngowe’, and ‘Tommy Atkins’). Combination of ran dom forest (RF) and first derivative spectra developed the predictive models. Factorial ANOVA examined the interaction effect of cultivar type, site (‘Thika’, ‘Embu’ and ‘Machakos), and fruit canopy position (sun exposed/within crown) on β-carotene, α-tocopherol and L-ascorbic acid contents. RF Models gave R2 = 0.97, RMSE = 2.27, RPD = 0.72 for β-carotene; R2 = 0.98, RMSE = 0.26, RPD = 0.30 for α-tocopherol and R2 = 0.96, RMSE = 0.51, RPD = 1.96 for L-ascorbic acid. Generally cultivar type affected vitamin C, F (3, 282) = 7.812, p < 0.05. Apple and Tommy Atkins had higher mean vitamins than Ngowe and Kent. In Machakos, within canopy fruits had higher β-carotene than sun-exposed fruits, F (5, 257) = 2.328, p = 0.043. However, interactions between fruit position, site and cultivar did not affect α-tocopherol and vitamin C. In Thika, Tommy Atkins at fully ripe stage had higher vitamin C than at intermediate maturity stage, F (2, 143) = 7.328, p = 0.01. These results show that FTIR-DRIFTS spectroscopy is a high-throughput method that can be used to predict mango fruit vitamins of in a large data set.